2021
DOI: 10.3389/fpls.2021.702892
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Growth Regulator Sprays Induced Tolerance to Combined Heat Stress by Enhancing Physiological and Biochemical Responses in Rice

Abstract: Rice yield has decreased due to climate variability and change in Colombia. Plant growth regulators have been used as a strategy to mitigate heat stress in different crops. Therefore, this study aimed to evaluate the effect of foliar applications of four growth regulators [auxins (AUX), brassinosteroids (BR), cytokinins (CK), or gibberellins (GA)] on physiological (stomatal conductance, total chlorophyll content, Fv/Fm ratio, plant canopy temperature, and relative water content) and biochemical (Malondialdehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 77 publications
3
9
0
Order By: Relevance
“…The results are in line with the works of Barutçular et al [32], who stated that a decline in chlorophyll content was a sign of aging processes, similarly to stressful conditions generated by high temperature [33]. The SPAD index changes observed in our study (Figure 1B) are consistent with the work of Pantoja-Benavides et al [34], who found that biostimulatory treatment increased chlorophyll content in the leaves of rice plants, thus positively contributing to heat stress tolerance.…”
Section: Discussionsupporting
confidence: 93%
“…The results are in line with the works of Barutçular et al [32], who stated that a decline in chlorophyll content was a sign of aging processes, similarly to stressful conditions generated by high temperature [33]. The SPAD index changes observed in our study (Figure 1B) are consistent with the work of Pantoja-Benavides et al [34], who found that biostimulatory treatment increased chlorophyll content in the leaves of rice plants, thus positively contributing to heat stress tolerance.…”
Section: Discussionsupporting
confidence: 93%
“…We observed increased MDA content in the control and the treatment sprayed with tap water. High-temperature stress increased MDA content in French beans ( Babu and Devraj, 2008 ) and rice ( Pantoja-Benavides et al, 2021 ). Under normal sowing conditions (November sown), a well-coordinated and responsive antioxidant system balanced oxidative damage to cellular components.…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary experiment was carried out to evaluate the effect of the number of foliar sprays (1, 2, or 3 sprays) of two plant hormones (cytokinins vs. brassinosteroids) on the mitigation of combined heat stress in the seedling stage. The compounds to be applied were determined based on the results obtained in a previous experiment ( Pantoja-Benavides et al., 2021 ). In this trial, rice plants of the genotype F2000 were initially divided into eight different treatment groups in which the conditions of heat stress and number of applications of CK and BR were combined.…”
Section: Methodsmentioning
confidence: 99%